Development and Initial Implementation of Performance Assurance Work Order Prioritization System - Bzovey, Chris; Moore, Michael; Krivoy, Agustina; Kresta, Petr; Gaamangwe, Tidimogo (CMBES Proceedings, 2016)
The implementation of an effective performance assurance (PA) system requires appropriate risk-based prioritization and optimization processes. Although a number of prioritization models have been developed, there are no generally accepted risk-based guidelines for prioritization of PA inspections. This paper presents a data and risk-based system for prioritizing PA inspection work orders. The developed system analyzes two parameters; the PA risk level of the device and the number of PA inspections missed, to determine the work order escalating factor and the priority level. To the best of our knowledge, incorporating the number of missed inspections in escalating inspections has not been extensively investigated. The system contributes to increasing inspection completion rates and optimizing resource utilization. The development and implementation of the system are presented, as well as opportunities for further development.